Rising distrust: Digital media dethrones mainstream media - Philips, Joseph; Subramani, R (AWARI, 2024)
In the contemporary era, news reports are subject to intense public scrutiny due to the global credibility audit. This decline in public confidence in news poses a grave challenge to journalists, as their credibility is at stake. This decline is believed to be a consequence of the prevailing discontent and dismay with the contemporary journalism ecosystem, leading to a shift in public preference from mainstream media to social media as a news source. These trends have been in effect for over a decade and have profoundly impacted the digital landscape. Consequently, the central objective of this study is to comprehensively assess the profound shift in individuals' propensity to consume news, both through traditional channels and alternative online sources. The role of populism and polarization in eroding the integrity of journalism cannot be overlooked. The central inquiry of our study is to ascertain the existence of a nexus between the escalated use of social media and the pervasive mistrust in news or among consumers of news. To this end, we have employed the online survey of English-speaking internet users' tendencies commissioned by the Reuters Institute Digital News 2019 and 2021 reports. These reports have revealed that educated youth residing in cities extensively utilize Facebook, WhatsApp, and other platforms as their primary source for accessing online news, accompanied by a notable rise in distrust. This phenomenon endangers the long-term viability of mainstream media outlets, and the decline in objectivity observed in Indian media lends credibility to this concern.